A Novel Aerodynamic Noise Reduction Method Based on Improving Spanwise Blade Shape for Electric Propeller Aircraft - Yuhang Wu; Yan-ting Ai; Wang Ze; Tian Jing; Xiang Song; Yingtao Chen (International Journal of Aerospace Engineering)
Aiming at the problem of excessive propeller noise in a new type of electric aircraft, in order to ensure the propeller aerodynamic characteristics simultaneously, a noise reduction method for improving the shape of the blade along the spanwise is proposed. The FW-H model, the unsteady slip mesh, and the large eddy simulation method are investigated to obtain the aerodynamic noise spectrum. Initially, through propeller aerodynamic noise numerical simulation, we obtain the sound pressure and aircraft aerodynamic noise in frequency domain. Subsequently, the effectiveness of our method is verified by comparing the experimental data and numerical results. Based on the established calculation model and method, under three different rotation speeds, the distribution law of the sound pressure level of the propeller with different shapes along the spanwise is analyzed, and the influence of the blade shape on the aerodynamic noise of the propeller is obtained. The research shows that the aerodynamic noise of the new blade compared to the original blade is significantly reduced at the same rotation speed higher than 1000 rpm, indicating that the blade load noise plays a dominant role in the aerodynamic noise and can be effectively reduced by changing the blade shape along the spanwise, thus reducing the aerodynamic noise of the blade.